2015
DOI: 10.1590/1982-43272562201505
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Validity for the Portilho/Banas Teaching Style Questionnaire

Abstract: The use of instruments with evidence of validity in education research brings advances to the production of knowledge. This article reports the stages of a survey of teaching style and the evidence for its validity. One thousand teachers participated in a study of different levels of education. An exploratory factor analysis indicated a structure of four factors in which 55 items had a factorial load greater than .30. The correlation steps made it possible to identify how the four factors are related to each o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
2
0
3
Order By: Relevance
“…El propósito de este trabajo es realizar los análisis necesarios para validar el instrumento sobre estilos de enseñanza de Portilho/Banas (Batista, Portilho y Rufini, 2015) tras su traducción al castellano y adaptación al contexto educativo español en profesores de Educación Infantil, Primaria, Secundaria, Bachillerato y Universidad a través del análisis de diversos procedimientos estadísticos que se explican a continuación.…”
Section: Armonización Y Sinergiaunclassified
See 2 more Smart Citations
“…El propósito de este trabajo es realizar los análisis necesarios para validar el instrumento sobre estilos de enseñanza de Portilho/Banas (Batista, Portilho y Rufini, 2015) tras su traducción al castellano y adaptación al contexto educativo español en profesores de Educación Infantil, Primaria, Secundaria, Bachillerato y Universidad a través del análisis de diversos procedimientos estadísticos que se explican a continuación.…”
Section: Armonización Y Sinergiaunclassified
“…La muestra para la validación estaba formada por 1000 profesores de diferentes niveles de enseñanza. El análisis factorial exploratorio mediante componentes principales, indicó una estructura de cuatro factores en los que se agruparon 40 ítems de escala Likert (Batista, Portilho y Rufini, 2015). Estas componentes dan lugar a cuatro estilos de enseñanza (dinámico, analítico, sistemático y práctico), considerando 10 ítems por estilo.…”
Section: Cuestionario Portilho/banas Estilos De Enseñanzaunclassified
See 1 more Smart Citation
“…Both Dunn and Dunn (1979) and also Stitt-Gohdes (2001) indicated that instructors teach in the way that they themselves learn more effectively. In the literature, learning styles have been defined as the mediation behavior of an instructor on both students' and instructors' cognitive characteristics (Butler, 1984); the behaviors of an instructor displayed when teaching a course and interacting with their students (Bennet, 1979); a presumptive structure associated with the cluster of an instructor's behaviors (Conti, 1985); the instructor's interaction with students that demonstrates their interest and the provision of support (Hilligoss, 1992); a predisposition towards the attitudes and purposes based on personal and social history and culture, in the teaching-learning transaction (Whittington and Raven, 1995); an instructor's behaviors based on their beliefs and habits, which leads the instructor to guide their thoughts and actions within the classroom (Heimlich and Norland, 2002); and as a set of behaviors and processes that are triggered within each step of the teaching process (Batista, Portilho, and Rufini, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Guven et al (2016) 2005). One more recent inventory can be also added to this list, which is the Portilho/Banas Teaching Style Inventory (Batista et al, 2015).…”
Section: Introductionmentioning
confidence: 99%